The impact of vitamin D deficiency on patients undergoing kidney transplantation: focus on cardiovascular, metabolic, and endocrine outcomes - Sarno, Gerardo; Daniele, Giuseppe; Tirabassi, Giacomo; Chavez, Alberto O; Ojo, Opeolu O; Orio, Francesco; Kahleova, Hana; Balercia, Giancarlo; Grant, William B; De Rosa, Paride; Colao, Annamaria; Muscogiuri, Giovanna (Endocrine, 2015)
Vitamin D deficiency is common among kidney transplant (KT) recipients because of reduced sunlight exposure, low intake of vitamin D, the immunosuppressive drug regimen administered, and steroid therapy. Glucocorticoids regulate expression of genes coding for enzymes that catabolize vitamin D, further reducing its level in serum. Although vitamin D primarily regulates calcium homeostasis, vitamin D deficiency is associated with the risk of several diseases, such as diabetes mellitus and tuberculosis. Aim of this review is to highlight endocrine and metabolic alterations due to the vitamin D deficiency by evaluating the mechanisms involved in the development of KT-related disease (cardiovascular, bone mineral density, and new-onset diabetes after transplantation). Next, we review evidence to support a link between low vitamin D status and KT-related diseases. Finally, we briefly highlight strategies for restoring vitamin D status in KT patients.
Keywords: Cardiovascular Diseases; Bone Density; Cardiovascular disease; Humans; lidé; Kidney transplantation; New-onset diabetes after transplantation; Vitamin D; vitamin D; diabetes mellitus; kostní denzita; Vitamin D Deficiency; Diabetes Mellitus; transplantace ledvin; Kidney Transplantation; Postoperative Complications; kardiovaskulární nemoci; Malignancies; Bone mineral density; pooperační komplikace; nedostatek vitaminu D